Pharmacokinetic Considerations for Combining Antiretroviral Therapy, Direct‐Acting Antiviral Agents for Hepatitis C Virus, and Addiction Treatment Medications. Issue 2 (March 2017) - Bednasz, Cindy J.; Venuto, Charles S.; Ma, Qing; Morse, Gene D.
Abstract: There are many factors that can affect the pharmacokinetics (PK) of drugs. Pathophysiological changes from disease states can alter the mechanisms that control the PK of antiretrovirals (ARVs), direct‐acting antivirals (DAAs), and addiction treatment medications. Drug–drug interaction pathways of certain ARVs and DAAs can be very complex, with agents being substrates, inhibitors, or inducers of multiple metabolic and transporter pathways. Buprenorphine and methadone may be used in HIV‐ and hepatitis C virus (HCV)–infected patients and may also be affected by drug interactions. Current research is focused on novel PK analyses, which aim to describe the PK of agents within organs that host the infection of interest, such as within hepatocytes during treatment for HCV. Modeling techniques allow for the prediction of drug PK in specific organs and the plasma compartment. This review will provide a summary of these areas while exploring PK considerations for ARVs, DAAs, and addiction treatment medications.